Building Innovation Capability in Organizations : an International Cross-Case Perspective. - Terziovski, Mile (Series on technology management., 2007)
Global competition, shorter product lifecycles and increasingly demanding customers are creating significant pressures for the creation of innovative organizations. By examining eight case studies in various industry sectors in Europe, Australia, Japan and Thailand, this book provides a qualitative explanation of the complex relationships between innovation capability, e-commerce, sustainable development and new product development. The book explores how organizations develop innovation capability through the application of e-commerce, sustainable development-orientation, and new product devel.